Le duel de Jean-Paul Sartre - Modrzejewska, Krystyna (Romanica Silesiana)
An enthusiast of Nathalie Sarraute’s writings, Jean-Paul Sartre convinced the author that her first novel Portrait d’un inconnu (1948) would not have found a publisher unless he wrote a preface to it. While underscoring her original writing technique, Sartre used terms and expressions that render the receptions of the novel considerably unfaithful to Sarraute’s intentions. Sarraute repeatedly commented upon it, admitting she would prefer to have written an article about the novel by herself, according to Sartre’s earlier promise. Key words: Sarraute, narrator, tropism, roman, others.